PENGARUH KESELAMATAN KERJA, DISIPLIN KERJA DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA NINJA XPRESS - NOVAL, I MADE MAI; KIRANA, PUTU HESTY WIDHI (Universitas Mahasaraswati K. Mataram, 2024)
This research focuses on the work productivity of Ninja Xpress Singaraja employees. This study uses a quantitative approach. The data collection technique used in this research is in the form of a questionnaire with a measuring instrument in the form of a Likert Scale. The population in this study were Ninja Xpress Singaraja employees with a population of 39 people. Sampling was carried out using the non-probability sampling technique chosen, namely purposive sampling, where those selected as respondents were 35 Ninja Xpress Singaraja courier employees. The data analysis technique used in this research is SPSS 16.0 (Statistical Package For The Social) software. Data analysis was carried out using multiple linear regression analysis techniques, showing that work safety has a positive and significant influence on the work productivity of Ninja Xpress Singaraja employees, shown by the sig value. 0.012 < 0.05, the work discipline used in this research has a positive and significant influence on the work productivity of Ninja Xpress Singaraja employees as shown by the sig value. 0.002 < 0.05, The incentive used in this research has a positive and significant influence on the work productivity of Ninja Xpress Singaraja employees as shown by the sig value. 0.016 <; 0.05 and work safety, work discipline and incentives (simultaneously) have a positive and significant influence on the work productivity of Ninja Xpress Singaraja employees with a value of f_count 37.472 > f_table